Resocialization and social reintegration of the adolescent offender by internation in youth center with family upright - Bermúdez Tapia, Manuel (2023)
The objectives and scope of the Code of Criminal Responsibility for Adolescents are dysfunctional when carrying out an evaluation of the jurisprudence of the Inter-American Court of Human Rights applicable to the stage of rehabilitation, resocialization and social reintegration applicable to «adults convicted of committing crimes» and to those «adolescent offenders», regarding the obligations of the State to provide procedural and constitutional guarantees to adolescent offenders in criminal proceedings when there are few Youth Centers where a socio-educational measure of hospitalization can be carried out. Consequently, a family uprooting is generated that limits the rights of these minors in the stage of execution of a sanction that in time is disproportionate and contradictory to the principles detailed in the Preliminary Title of the aforementioned norm.